Genetic diversity and population structure of cotton (Gossypium hirsutum L. race latifolium H.) using microsatellite markers - Domingos Moiana, Leonel (2012)
Cotton (Gossypium spp.) is the world?s leading natural fiber crop and is cultivated in diverse temperate and tropical areas. The proper use of cotton genetic resources allows breeders to identify and select superior parents for breeding programs. In this sense, molecular markers are important tools for polymorphism identification in genetic diversity analyses. The objective of this study was to evaluate genetic diversity and population structure in tetraploid cotton (Gossypium hirsutum L. race latifolium H.) by means of microsatellite markers. 43 cultivars and inbred lines from Africa, United States and Brazil were analyzed. From a total of 33 SSRs markers, 15 markers revealed 104 polymorphic SSR alleles. Four groups were identified applying different methods (the probabilistic method, principal coordinates analysis and neighbor joining tree). American cultivars and inbred lines were included in group I; African cultivars in group II; and Brazilian cultivars in groups II, III and IV. The FST index indicated high genetic variability among the cultivars and inbred lines studied. In general, American cultivars were the most divergent in relation to African and Brazilian ones. The dissimilarity index ranged from 0.06 to 0.90 and the lowest genetic divergence was observed between TAMCOT22 and TAM96WD-69s(L). Combination of American cultivars and inbred lines with African and Brazilian cultivars is recommended to obtain superior transgressive segregants in order to improve yield in cotton breeding programs.